The Future of the Eurozone: How to Keep Europe Together: A Progressive Perspective from Germany - Steinberg, Philipp; Schellinger, Alexander (transcript, 2017)
Europe is stumbling from crisis to crisis. The financial and debt crises are endangering the European currency union; referenda in several EU countries show widespread Euroscepticism; the economy is only slowly regaining momentum; unemployment remains high in many Member States; and the refugee crisis has deepened political divisions. We need an answer to the question of how to rescue the Euro and keep Europe together. In this volume, renowned German researchers and leading practitioners provide pragmatic recommendations. Their plea for a democratically legitimized Euro Finance Minister, a new economic approach, a common Eurozone budget, and minimum social standards are the prerequisites for a fair, stable, and prosperous Europe.